Ultimate capacity of I-sections under combined loading – Part 2: Parametric studies and CSM design. (September 2018) - Yun, X.; Gardner, L.; Boissonnade, N.
Abstract: The second part of the study on the ultimate capacity of hot-rolled steel I-sections under combined compression and bending moment, focussing on parametric studies and design, is presented herein. An extensive numerical parametric study was carried out, using the verified finite element (FE) models from the companion paper, to generate further structural performance data for specimens with different steel grades, cross-section slendernesses and loading cases. The numerical results together with the experimental results were then used to assess the accuracy of two codified design methods: the European Standard EN 1993-1-1 (2005) and the American Specification AISC-360-16 (2016). The design strengths predicted by the current design standards were found to be generally rather conservative and scattered when applied to non-slender cross-sections, owing principally to the neglect of material strain hardening and reserve capacities between the classification limits. To improve the accuracy and efficiency of the design rules, the continuous strength method (CSM) – a deformation-based design approach which relates the resistance of a cross-section to its deformation capacity – was extended to cover the design of hot-rolled steel I-sections under combined loading, underpinned by both the experimentally and numerically derived ultimate capacities. Overall, the CSM was shown to offer more accurate and consistent predictions than the current design provisions. Finally, reliability analysis was performed to evaluate the reliability level of the design rules. Highlights: Validated FE models have been used to perform parametric studies on hot-rolled steel I-sections under combined loading. Current design provisions in have been assessed using the experimentally and numerically derived data. The CSM has been extended to cover the design of hot-rolled steel I-sections under combined loading. The reliability of the CSM has been evaluated by means of statistical analyses according to EN 1990.